Evaporation of nanofluid droplets on heated surfaces - Choong, Yue Hao (2015)
Nanofluids are dilute liquid suspensions of nanoparticles which have garnered much interest in the recent decade due to their enhanced thermal properties over traditional heat transfer fluids such as water, oil and ethylene glycol. This makes nanofluids ideal for multiple evaporative cooling applications within the industry with remarkable potential savings in terms of energy usage. The aim of this project is to investigate underlying factors affecting the rate of sessile nanofluid droplet evaporation so that nanofluids may be more efficiently utilised within the industry. Three main studies investigating the effects of nanoparticle concentration, size and surface wettability on evaporation rate were conducted. The first study showed that an optimum concentration of nanoparticles exists. Too high concentrations of nanoparticles could lead to detrimental results. The second study showed that a smaller nanoparticle size leads to a faster evaporation rate. However, it is necessary to prevent agglomeration of the nanoparticles within the suspension mixture or thermal performance could suffer. The third study showed that better wettability results in faster evaporation rate. The evaporation kinetics of hydrophilic and hydrophobic surfaces also differ greatly, with evaporation rate on hydrophobic surfaces up to four times as slow as hydrophilic surfaces. Some future work that could be carried out are investigation into prevention of agglomeration of nanoparticles, internal flows of droplets during evaporation, evaporation on hydrophobic surfaces due to non-linear behaviour, and quantifying surface roughness on evaporation characteristics using a surface roughness gauge.